Análisis geohistórico del tren turístico: Ruta del Hielo - Buenaño Cuello, Javier Heriberto (2021)
The objective of this research is to analyze geo-historical aspects of the Tourist Train: Ice Route from a cartographic perspective with a historical vision, in order to highlight all the geomorphological characteristics, historical events and economic impacts that comprise the Ice Route. The research work details the location of geographic spaces through which the Tourist Train: Ice Route crosses, as well as the geomorphological characteristics present in the different landscapes. It also contrasts the historical significance of the Ice Route in relation to the Route of the Icemen. The research is non-experimental with a qualitative approach, the data was acquired through maps, topographic charts, oral, iconographic, written sources, materials, among others; The analysis was carried out using the geographic and historical method. In the discussion of the results, the geographic spaces and the geomorphological characteristics of each landscape present in the Ice Route are shown, as well as the historical significance of the tourist train and the economic impact caused by the liquidation of the railroad on the inhabitants of Urbina, pointing out the most affected production sectors and the average calculation of economic losses in the entrepreneurs of the museum located in this station.